Improving Co-operation between Tax Authorities and Anti-Corruption Authorities in Combating Tax Crime and Corruption - World Bank (Paris: Organisation for Economic Co-operation and Development, and the World Bank, 2018)
This joint report by the World Bank and OECD identifies building blocks for more effective co-operation and is the first comprehensive global study of its kind. The content of the report is based on responses from 67 countries to a survey, which examined the organizational structure for investigating and prosecuting tax crime and corruption, as well as models for, and the experience of, inter-agency co-operation in fighting these crimes. The report found that further efforts are warranted to improve interagency cooperation, as only 55 percent of the surveyed countries require corruption investigators to report suspected tax crimes. And when it comes to information-sharing, even fewer countries mandate it — just 44 percent. The report presents a variety of lessons for overcoming barriers to cooperation and modalities through which cooperation can be effectuated.